An investigation into the feasibility of incorporating didanosine into innovative solid lipid nanocarriers - Wa Kasongo, Kasongo (Rhodes University, Faculty of Pharmacy, Pharmacy, 2010)
The research undertaken in these studies aimed to investigate the feasibility of developing and manufacturing innovative solid lipid carriers, such as solid lipid nanoparticles (SLN) and/or nanostructured lipid carriers (NLC) using a hot high pressure homogenization method, for didanosine(DDI). In addition, studies using in vitro differential protein adsorption were undertaken to establish whether the SLN and/or NLC have the potential to deliver DDI to the central nervous system (CNS). Prior to initiating pre-formulation, formulation development and optimization studies of DDI-Ioaded SLN and/or NLC, it was necessary to develop and validate an analytical method for the in vitro quantitation and analysis of DDI. An accurate, precise and sensitive RP-HPLC method with UV detection set at 248 nm was developed, optimized and validated for the quantitative in vitro analysis of DDI in formulations. Pre-formulation studies were designed to evaluate the thermal stability of DDI and to select and characterize lipid excipients that may be used for the manufacture of the nanocarriers. It was established that DDI is thermostable at temperatures not exceeding 163°C and therefore a hot high pressure homogenization technique could be used to manufacture DDI-loaded SLN and/or NLC. Lipid screening studies revealed that DDI is poorly soluble in both solid and liquid lipids. A combination of Precirol® ATO 5 and Transcutol® HP was found to have the best solubilizing-potential for DDI of all lipids investigated. The inclusion of Transcutol® HP into Precirol® ATO 5 changed the polymorphic form of the solid lipid from the stable 13-modification to a material that exhibited the co-existence between α- and β-polymorphic forms. The relatively high solubility of DDI in Transcutol® HP compared to Precirol® ATO 5 was an indication that a solid lipid matrix prepared from a binary mixture of Precirol® ATO 5 and Transcutol® HP was likely to have a higher loading capacity and encapsulation efficiency for DDI than a matrix consisting of Precirol® ATO 5 alone. Furthermore, the potential for the solid lipid matrix to exist in the α- and/or β-modifications when Transcutol® HP was added to Precirol® ATO 5 suggested that expulsion of DDI from a solid lipid matrix during prolonged storage periods was likely to be minimal. Therefore it was considered logical to investigate the feasibility of incorporating DDI into NLC and not in SLN. However, due to the limited solubility of DDI in lipids, formulation development of DDI-loaded NLC commenced using small quantities of DDI. Formulation development and optimization studies of DDI-loaded NLC were initially aimed at selecting a surfactant system that was capable of stabilizing NLC in an aqueous environment. Solutol® HS alone or a ternary mixture consisting of Solutol® HS, Tween® 80 and Lutrol® F68 was found to stabilize the nanoparticles in terms of particle size and the polydispersity index. The use of the ternary mixture as the surfactant system was preferred to using Solutol® HS alone as Lutrol® F68 and especially Tween® 80 have been successfully used to target the delivery of API to the brain. Aqueous DDI-free and DDI-Ioaded NLC containing increasing amounts of DDI were manufactured using hot high pressure homogenization at 800 bar for three cycles. The NLC formulations were characterized in terms of particle size, polydispersity index, zeta potential, and polymorphism, degree of crystallinity, encapsulation efficiency (EE), shape and surface morphology. The mean particle size for all formulations was below 250 nm with narrow polydispersity indices, indicating that narrow particle size distribution had been achieved. The d99% values for all formulations tested, were generated using laser diffractometry, and were below 400 nm, with span values ranging from 0.84 - 1.19 also suggesting that a narrow particle size distribution had been achieved. The zeta potential values measured in double distilled water with the conductivity adjusted to 50 μS/cm ranged from -18.4 to -11.4 mV. In addition, all the formulations showed a decrease in the degree of crystallinity as compared to the bulk lipid material and WAXS shows that the formulations existed in a single β-modification form. Furthermore DDI that had been incorporated into the NLC appeared to be molecularly dispersed in the lipid matrices. These parameters remained unaffected for most formulations following storage for two months at 25°C. In addition these formulations contained a mixture of spherical and non-spherical particles irrespective of the amount of DDI that was added during the manufacture of the formulations. These studies showed that it was feasible to develop and incorporate small amounts of DDI into NLC. However in order to use these delivery systems for oral administration of DDI to paediatric patients, strategies to improve the amount of DDI that could be loaded into the particles and to achieve high encapsulation efficiencies had to be developed. The limited solubility of DDI in lipid media was identified as a major factor that affected the loading capacity and encapsulation efficiency of DDI in the NLC. Therefore, a novel strategy aimed at increasing the saturation solubility of DDI in the lipid by attempting to increase the dissolution velocity of the drug in the lipid using a particle size reduction approach, was designed and investigated. DDI was dispersed in Transcutol® HP and the particle size of DDI in the liquid lipid medium was reduced gradually using hot high pressure homogenization and the product obtained from these studies was used to manufacture DDI-loaded NLC using a cold high pressure homogenization procedure. Although the encapsulation efficiency and drug loading following use of this approach was relatively high, the particles were large and showed a tendency to grow in size leading to the formation of microparticles after storage for two months at 25°C. In addition, the degree of crystallinity of the nanoparticles increased rapidly over the same storage period which led to expulsion of DDI nanoparticles for the NLC, despite the DDI loading in NLC being unaffected. It was clearly evident that this new approach of manufacturing solid lipid nanocarriers could be used as a platform not only for enhancing the loading capacity of DDI in solid lipid nanocarriers but also for other hydrophilic drugs. Differential protein adsorption patterns of DDI-loaded NLC were generated in vitro using two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) in order to establish the potential for these systems to deliver DDI to the CNS. NLC formulations containing small amounts of DDI were used as these formulations showed a better stability profile than the formulation with a higher encapsulation efficiency and drug loading capacity. Furthermore, the encapsulation efficiency and drug loading of DDI were considered sufficient for use in 2-D PAGE studies. Data obtained from 2-D PAGE analysis reveal that DDI-loaded NLC preferentially adsorb proteins in vitro that are responsible for specific brain targeting in vivo. More importantly, these studies reveal that in addition to Tween® 80 that has already been shown to have the potential to target CDDS to the brain, Solutol® HS 15 has the potential to achieve a similar objective. Consequently, DDI-loaded NLC have the potential to deliver DDI to the brain and these results may be used as a platform for conducting in vivo studies to establish whether DDI can cross the blood brain barrier and enter the CNS when administered in NLC which may in turn lead to a major breakthrough in the management of HIV/AIDS and Aids Dementia Complex (ADC).
Keywords: Antiretroviral agents; HIV infections -- Drug testing; Didanosine; Nanoparticles; Drug delivery systems; Nanostructured materials; Lipids -- Therapeutic use